2015
DOI: 10.1186/s12866-015-0506-5
|View full text |Cite
|
Sign up to set email alerts
|

Two nucleotide second messengers regulate the production of the Vibrio cholerae colonization factor GbpA

Abstract: BackgroundThe nucleotide second messengers cAMP and c-di-GMP allow many bacteria, including the human intestinal pathogen Vibrio cholerae, to respond to environmental stimuli with appropriate physiological adaptations. In response to limitation of specific carbohydrates, cAMP and its receptor CRP control the transcription of genes important for nutrient acquisition and utilization; c-di-GMP controls the transition between motile and sessile lifestyles often, but not exclusively, through transcriptional mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 76 publications
0
19
0
Order By: Relevance
“…The 423-bp ilvC promoter region was amplified with OSD107 and OSD108 (27). As a negative control, a 133-bp fragment of the gbpA gene was amplified from V. cholerae C6706 chromosomal DNA with primers gbpAqF and gbpAqR (103). Binding reactions between CodY and putative target DNA took place in a mixture of 20 mM Tris (pH 8); 50 mM sodium glutamate; 10 mM MgCl 2 ; 5 mM EDTA; 0.1% Tween 20; 5% glycerol; 2 mM GTP; and 100 mM each leucine, isoleucine, and valine (30).…”
Section: Methodsmentioning
confidence: 99%
“…The 423-bp ilvC promoter region was amplified with OSD107 and OSD108 (27). As a negative control, a 133-bp fragment of the gbpA gene was amplified from V. cholerae C6706 chromosomal DNA with primers gbpAqF and gbpAqR (103). Binding reactions between CodY and putative target DNA took place in a mixture of 20 mM Tris (pH 8); 50 mM sodium glutamate; 10 mM MgCl 2 ; 5 mM EDTA; 0.1% Tween 20; 5% glycerol; 2 mM GTP; and 100 mM each leucine, isoleucine, and valine (30).…”
Section: Methodsmentioning
confidence: 99%
“…A second line of evidence in the literature ties cellulose-dependent aggregation to environmental signals via highly conserved role of secondary messenger c-di-GMP (cyclic di-GMP) (46,47). Nutrient limitation such as carbohydrate starvation is frequently correlated with increased c-di-GMP levels in heterotrophs (48); carbohydrate starvation results in both nutrient and energy limitation in heterotrophs. The cyanobacterium Thermosynechococcus vulcanus RKN undergoes cellulose-dependent aggregation in response to blue light (40,44), an energy-limited condition, in a process requiring formation of c-di-GMP by the protein SesA (Tlr0924).…”
mentioning
confidence: 99%
“…Genome neighborhood analysis revealed that gbpA is near two c-di-GMP binding riboswitches called Vc1 and Vc2 (130). A recent study confirmed that the second messengers c-di-GMP and cyclic AMP (cAMP) regulate gbpA transcription (131). The levels of c-di-GMP and cAMP are regulated by numerous abiotic signals, confirming that GbpA expression is fine-tuned in response to environmental signals (131).…”
Section: Role Of Pmos In Human Infectionmentioning
confidence: 97%